ETIKA IDENTITAS - Gadis Arivia (Litbang STFT Widya Sasana Malang, 2009)
Identity groups occupy the public space in Indonesia and it has also created an uneasy space in democracy. In a democracy, identity groups are minority groups that seeks protection from the State. However in Indonesia, identity groups mainly belong to the majority who demand greater representation and power. Do group identities cause constrain rather than liberate individuals? How can identity groups respect human rights? This article explores the importance of ethics in identity and rejects politics of identity